Experimental Study on the Relationship Between Cavitation and Lift Fluctuations of S-Shaped Hydrofoil - Liu, Haiyu; Lin, Pengcheng; Tang, Fangping; Chen, Ye; Zhang, Wenpeng; Yan, Shikai (Frontiers in Energy Research, 2021)
In order to study the energy loss of bi-directional hydraulic machinery under cavitation conditions, this paper uses high-speed photography combined with six-axis force and torque sensors to collect cavitating flow images and lift signals of S-shaped hydrofoils simultaneously in a cavitation tunnel. The experimental results show that the stall angle of attack of the S-shaped hydrofoil is at ±12° and that the lift characteristics are almost symmetrical about +1°. Choosing α=+6° and α=-4° with almost equal average lift for comparison, it was found that both cavitation inception and cloud cavitation inception were earlier at α=-4° than at α=+6°, and that the cavitation length at α=-4° grew significantly faster than at α=+6°. When α=+6°, the cavity around the S-shaped hydrofoil undergoes a typical cavitation stage as the cavitation number decreases: from incipient cavitation to sheet cavitation to cloud cavitation. However, when α=-4°, as the cavitation number decreases, the cavitation phase goes through a developmental process from incipient cavitation to sheet cavitation to cloud cavitation to sheet cavitation to cloud cavitation, mainly because the shape of the S-shaped hydrofoil at the negative angle of attack affects the flow of the cavity tails, which is not sufficient to form re-entrant jets that cuts off the sheet cavitation. The formation mechanism of cloud cavitation at the two different angles of attack(α=+6°、-4°) is the same, both being due to the movement of the re-entrant jet leading to the unstable shedding of sheet cavity. The fast Fourier analysis reveals that the fluctuations of the lift signals under cloud cavitation are significantly higher than those under non-cavitation, and the main frequencies of the lift signals under cloud cavitation were all twice the frequency of the cloud cavitation shedding. There are also frequency components of approximately 200-800Hz in the frequency spectra, which may be caused by the vortex flow around the S-shaped hydrofoil.